1990
DOI: 10.1002/jcp.1041440209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β‐all‐trans retinoic acid on growth, proliferation, and cell death in a multicellular tumor spheroid model for squamous carcinomas

Abstract: The growth of multicellular tumor spheroids, MTSs, from squamous carcinoma line MDA 886Ln was inhibited by beta-all-trans retinoic acid (RA). Inhibition occurred within 3 to 5 days of treatment, and MTS size then remained static for up to 2 weeks. Although their growth stopped, 10-day-treated MTSs incorporated [3H]thymidine into trichloroacetic acid-precipitable material, and the [3H]thymidine labeling index, determined by autoradiography, was equivalent between control and RA-treated MTSs. Bivariate flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
2

Year Published

1994
1994
2000
2000

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 25 publications
0
6
2
Order By: Relevance
“…Several reports have shown that retinoids might inhibit neoplastic growth through the induction of apoptosis (Sacks et al, 1990;Atencia et al, 1994). This was demonstrated in various models of leukemia (Delia et al, 1993), neuroblastoma (Ponzoni et al, 1995), lung carcinoma (Kalemkerian et al, 1995) and recently also in breast-cancer cell lines (Zhi-Ming Shao et al, 1995).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several reports have shown that retinoids might inhibit neoplastic growth through the induction of apoptosis (Sacks et al, 1990;Atencia et al, 1994). This was demonstrated in various models of leukemia (Delia et al, 1993), neuroblastoma (Ponzoni et al, 1995), lung carcinoma (Kalemkerian et al, 1995) and recently also in breast-cancer cell lines (Zhi-Ming Shao et al, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Several reports have already indicated that retinoids exert their activities through the induction of apoptosis in many tumor cell types. (Sacks et al, 1990;Atencia et al, 1994).…”
mentioning
confidence: 99%
“…Their effects have been well studied in different cellular models of leukemia (Breitman et al, 1980), neuroblastoma (Sidell, 1982), squamous-cell carcinoma (Sacks et al, 1990) and breast carcinoma (Wetherall and Taylor, 1986;Toma et al, 1997;Bollag et al, 1997).…”
mentioning
confidence: 99%
“…These inhibitors include calcitriol, retinoic acid, and capsiacin (Sacks et al 1990, Hannun and Obeid 1995,Wolvetang et al 1996. These inhibitors include calcitriol, retinoic acid, and capsiacin (Sacks et al 1990, Hannun and Obeid 1995,Wolvetang et al 1996.…”
Section: Coenzyme Q Influence On Transmembrane Functionsmentioning
confidence: 99%